Structural analysis and design of a car carrier with composite sandwich deck panels. (3rd October 2019) - Andric, Jerolim; Kitarovic, Stanislav; Radolovic, Vito; Prebeg, Pero
ABSTRACT: The paper presents the main structural aspects of the innovative car carrier being designed and built by the Uljanik Shipyard as a Newbuilding 513-514. To increase deadweight and reduce structural mass, vertical centre of gravity and fuel consumptions, three upper fixed vehicles decks have been designed as a hybrid concept, i.e. a combination of steel deck grillage and composite sandwich panels. Various relevant aspects and results of the case study are undertaken with the aim to determine a feasible structural design of the lightweight, cost-effective and easily installable composite sandwich panels intended to carry vehicles loaded on fixed decks. For a predefined sandwich panel geometry and interaction with the supporting deck steel grillage, structural capability and compliance with the relevant Bureau Veritas (BV) rules of various feasible configurations were evaluated, whereby structural response was determined using the finite element method (FEM) on the local (panel) level. On the global level, composite sandwich panels do not contribute to the hull girder bending, so longitudinal and racking strengths of the new structural concept have been evaluated using the complete full ship FEM model. Finally, benefits of the suggested concept have been summarised and compared to the conventional car carrier design.